ANALISIS LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN CINANGKA KOTA DEPOK - Fifi Triana Sari; Budhi Prabowo (Journal of Research and Publication Innovation, 2025)
This study is entitled "Analysis of the Work Environment on Employee Performance in the Cinangka Village Office, Depok City". The aim of this research is to analyze the work environment at the Cinangka sub-district office, Depok City, then to analyze the work environment in improving the performance of Cinangka sub-district office employees. This research uses descriptive qualitative research methods, and the data collection techniques used are observation, interviews, documentation and FGDs as well as chain of evidence. Data analysis techniques use data reduction, data presentation, and drawing conclusions. This research was conducted on 5 Cinangka sub-district office employees including the sub-district head, sub-district secretary and sub-district employees. The results of this research obtained from researchers' interviews with the objects show employee perceptions that working environmental conditions, both physical and non-physical, have a significant effect on employee performance. Adequate facilities such as lighting, measurements and complete work equipment increase comfort, especially increasing cleanliness and tidiness as well as employee contribution. Apart from that, interpersonal relationships between employees and superiors also contribute to a positive work atmosphere. This research concludes that to improve employee performance, it is important for management to continue to pay attention to and improve the quality of the work environment at the Cinangka Village Office